Arus Kas Bebas dan Pengaruh Komitmen Pembelian dan Identitas Global pada Niat Beli Produk Fashion MewahNilai Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nadia Nurrahmah Sari; Ida Bagus Nyoman Udayana (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to explore the relationship and direct influence of luxury fashion on the purchase intention of luxury goods, the direct effect of purchase commitment on the purchase intention of luxury goods and the influence of global identity on the purchase intention of luxury goods. On an ongoing basis, companies can increase sales commitment behavior to engage buyers to generate interest in purchasing luxury goods. Purchase intention becomes one of the most important things in a company if a company shares information/knowledge behavior with customers, it will also increase the customer's interest in buying a product. These efforts can be realized in the form of increasing customer cognitive capital and being able to provide more services to customers. Data collected by 50 users of luxury Fahion products. The data that has been collected is then tested for validity, reliability test, hypothesis test and classic assumption test. The results showed that cognitive variables had a positive effect on information/knowledge sharing behavior, social interaction had a positive effect on information/knowledge sharing behavior, and information/knowledge sharing behavior had a positive effect on purchase intention. Keywords: purchase commitment, global identity, purchase intention of fashion products